Application of Lean Management Principles to Reduce Waste and Improve Operational Efficiency in the Service Sector - Radjawane, Louise Elizabeth; Darmawan, Didit; Varela, Jony Rodrigues (Journal of Social Science Studies, 2022)
The application of lean management principles in the service sector focuses on reducing waste and improving operational efficiency through time management, more effective resource management, and improved service quality. The service sector has unique challenges because it is more difficult to measure compared to the manufacturing sector. In the service sector, waste is often not obvious, such as customer waiting times or inefficient interactions, which can reduce service quality. The application of lean requires adaptation to service characteristics and the development of more complex indicators to measure performance. With the use of technology, employee engagement, and the application of lean principles such as value stream mapping, companies can identify waste and improve service process flow. Successful lean application will improve operational efficiency and service quality, which in turn will improve customer satisfaction and the company’s competitiveness in an increasingly competitive market.